The Significance of Name-Based Racial Composition in Analyzing Neighborhood Disparities - Karl Vachuska (Socius)
Contemporary sociological research emphasizes the need to analyze inequality beyond nominal categories. Although research has grown in this regard at the individual level, little research has pursued this approach with neighborhoods. This article explores how names can serve as a measure of the perceived typicality associated with race and how names are associated with neighborhood characteristics. Analyses on data with the names of over 300 million Americans demonstrate that name-based racial composition more fully explains socioeconomic disparities among neighborhoods than conventional survey-based racial composition metrics. Neighborhoods with the most Black-sounding names demonstrate greater socioeconomic disadvantage than neighborhoods with the most individuals self-identifying as Black. Additionally, naming patterns explain variation in socioeconomic inequality within both predominantly nominally Black neighborhoods and predominantly nominally White neighborhoods—where little nominal racial variation exists. This research suggests that infracategorical measures of race can provide additional predictive power to nominal measures of racial composition when analyzing neighborhood inequalities